Governance and responses of health and surveillance systems to COVID-19 in BRICS countries: A scoping review protocol - Adelyne Maria Mendes Pereira; Monique Azevedo Esperidião; Sílvia Karla Azevedo Vieira Andrade; João Felipe Marques Silva; Louise Celeste Rolim Silva; Adriano Silva; Isabela Barboza da Silva Tavares Amaral; Isabel Domingos Martinez dos Santos; Thalyta Cássia de Freitas Martins; Aline Degrave (PLoS ONE, 2025)
The capacity of countries to respond to COVID-19 has varied, worsening inequities. Structural factors (such as socio-economic inequalities and health system financing conditions) and political-institutional factors (such as the leadership and directionality of government action) have a major influence on the structure and outcomes of national responses. An effective COVID-19 response requires strong national governance, coordination strategies, and integration between health system actions and public health surveillance measures. This scoping review aims to synthesize the evidence on the governance and responses of the BRICS countries to the COVID-19 pandemic within a context of structural inequalities, identifying lessons and gaps in the current literature. This protocol was guided by the scoping review methodology, developed by the Joanna Briggs Institute, and used the PRISMA-P reporting guidelines. Searches will be carried out on the BVS Portal, Pubmed, Web of Science, Scopus, Embase and Dimensions databases. Inclusion criteria include secondary sources in the form of scientific publications, complemented by government and institutional documents published between 2020 and 2024. Exclusion criteria exclude publications that do not involve the selected countries, focus only on local or regional level without contemplating national-level elements, and/or address with COVID-19 solely from a clinical perspective. The scoping review process will select and organize retrieved data using the Rayyan software. Six independent reviewers will select the articles, working in three pairs. The results will be described, analyzed, and categorized through a descriptive synthesis, correlating them with the research objectives and questions. Registration This protocol is registered on the Open Science Framework (OSF) (available at https://doi.org/10.17605/OSF.IO/SN5ZY) and Figshare (available at https://doi.org/10.6084/m9.figshare.25908340) platforms.